(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2013)
هدف البحث إلى تعرّف واقع استخدام المسرح في مدارس مدينة دمشق الحكومية من وجهة نظر معلمي الحلقة الثانية، ووضع مقترحات تساعد في تفعيلها، تبعاً لمتغيرات البحث (الجنس، المؤهل العلمي، وسنوات الخبرة)، وتكونت عينة البحث من (405) معلماً ومعلمة، تم اختيارهم بالطريقة العشوائية البسيطة من مدارس مدينة دمشق الرسمية، حيث طُبقت استبانة واقع استخدام المسرح المدرسي، وهي من إعداد الباحث بعد التحقق من صدقها وثباتها. وأشارت النتائج إلى ما يلي: • عدم وجود فروق دالة إحصائياً بين متوسطات درجات المعلمين الذكور والمعلمين الاناث, على الدرجة الكلية لاستبانة واقع استخدام المسرح المدرسي. • وجود فروق دالة إحصائياً بين متوسطات درجات المعلمين الحاملين الشهادة الجامعية، ومتوسطات درجات المعلمين الحاملين شهادة معهد إعداد المدرسين، لصالح الجامعي. • وجود فروق دالة إحصائياً بين متوسطات درجات المعلمين أصحاب سنوات الخبرة، لصالح المعلمين الذين لديهم 6 سنوات فأكثر. This research aims at knowing the reality of School Theatre in Damascus city schools from the point of view of second stage teachers’ of basic education. In addition, it aims at researching some suggestions that help in activating the use of School Theatre according to variables of this research which are (gender, qualification and expertise). The sample consisted of (405) teachers who were selected from Damascus city schools by using the simple random sample. The researcher prepared a questionnaire related to the reality of School Theatre and it was applied on the sample after it was tested for its validity and reliability. The results indicated the following: • There were no statistical significant differences between the average of male teachers’ grades and the average of female teachers’ grades in relation to the total mark of the questionnaire of School Theatre reality. • There were statistical significant differences between the average of teachers’ grades whose qualifier was a university degree and the average of teachers’ grades whose qualifier was an institute certificate, where the difference was on the side of the teachers’ whose qualifier was a university degree . There were statistical significant differences between the average of teachers’ who possess expertise, where the difference was on the side of the teachers who have expertise of six years and more.